2005
DOI: 10.1128/jb.187.5.1724-1731.2005
|View full text |Cite
|
Sign up to set email alerts
|

Additional Determinants within Escherichia coli FNR Activating Region 1 and RNA Polymerase α Subunit Required for Transcription Activation

Abstract: The global anaerobic regulator FNR is a DNA binding protein that activates transcription of genes required for anaerobic metabolism in Escherichia coli through interactions with RNA polymerase (RNAP). Alaninescanning mutagenesis of FNR amino acid residues 181 to 193 of FNR was utilized to determine which amino acid side chains are required for transcription of both class II and class I promoters. In vivo assays of FNR function demonstrated that a core of residues (F181, R184, S187, and R189) was required for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…9 In the dimerized, [4Fe-4S] 2C -containing state, FNR binds site-specifically to DNA and interacts with RNA polymerase (RNAP) to regulate transcription from FNR-dependent promoters. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Both in vivo and in vitro studies have demonstrated that under aerobic conditions, the [4Fe-4S] 2C cluster is converted to a [2Fe-2S] 2C cluster, resulting in an inactive, monomeric form of FNR ([2Fe-2S] 2C -FNR). 8,10,23,24 The [2Fe-2S] 2C cluster is further destroyed under aerobic growth conditions, presumably as a result of its instability to superoxide, a by-product of aerobic metabolism, as demonstrated in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…9 In the dimerized, [4Fe-4S] 2C -containing state, FNR binds site-specifically to DNA and interacts with RNA polymerase (RNAP) to regulate transcription from FNR-dependent promoters. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Both in vivo and in vitro studies have demonstrated that under aerobic conditions, the [4Fe-4S] 2C cluster is converted to a [2Fe-2S] 2C cluster, resulting in an inactive, monomeric form of FNR ([2Fe-2S] 2C -FNR). 8,10,23,24 The [2Fe-2S] 2C cluster is further destroyed under aerobic growth conditions, presumably as a result of its instability to superoxide, a by-product of aerobic metabolism, as demonstrated in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas these four cysteine residues are perfectly conserved in AcpR from Azoarcus (at positions 18, 21, 27, and 122), in the AadR protein, only two cysteine residues (at positions 20 and 117) are conserved. The AR-1, AR-2, and AR-3 activation regions, which are involved in the interaction of the E. coli FNR protein with the ␣-C-terminal domain, ␣-N-terminal domain, and 70 -C-terminal domain subunits of RNAP, respectively (242,371), are also conserved in AcpR and AadR, although in the latter, there is low amino acid sequence conservation at the AR-1 region (97). A new branch of the FNR/CRP superfamily that has recently emerged includes transcriptional regulators such as CprK ( Table 3) that mediate the response to halogenated aromatic compounds in the dehalorespiration of different Desulfitobacterium strains (286).…”
Section: Overimposed Regulationmentioning
confidence: 99%
“…Fnr, also named OxrA in Salmonella, is a cytoplasmic oxygen sensor that can bind promoter sequences, and interacts with the RpoA subunit of RNA polymerase to increase the efficiency of transcription of a variety of genes required for anerobic metabolism, while it represses many of the genes encoding enzymes involved in aerobic electron transport, oxidative phosphorylation and some tricarboxylic cycle enzymes (Unden et al, 1995;Wei & Miller, 1999;Perrenoud & Sauer, 2005;Weber et al, 2005).…”
Section: D Gel Electrophoresis Analyses By Vanmentioning
confidence: 99%